Asymmetry of knowledge spillovers between MNCs and host country firms - Singh, Jasjit (Journal of International Business Studies, 2007)
We use patent citation data to examine knowledge flows between foreign multinational companies (MNCs) and host country organisations in 30 countries. We find not just significant knowledge inflows from foreign MNCs to host country organisations, but also significant outflows back from the host country to foreign MNCs. In fact, in technologically advanced countries, knowledge outflows to foreign MNCs greatly outweigh knowledge inflows. Even in technologically less advanced countries, knowledge outflows are only slightly weaker than inflows. Additional analysis shows that the exact pattern varies across sectors within a country, depending on the country's expertise in individual sectors. Finally, knowledge inflows and outflows appear to track personnel flows between foreign MNCs and host country organisations.